El reconocimiento voluntario, judicial y testamentario en los derechos del reconocido - Mendoza Yungán, Margoth Fernanda (2018)
The research entitled: "VOLUNTARY, JUDICIAL AND TESTAMENTAL RECOGNITION IN THE RIGHTS OF THE RECOGNIZED.", Is divided into three important parts, first begins by referring the problem, as well as the general and specific objectives to be demonstrated, then poses the justification of work, to finally refer the state of art; that is, the writers who have investigated a similar topic, briefly explaining that the content of their research is included. Next, the theoretical framework is carried out, which contains all the theoretical doctrinal part of the investigation, within this section the recognition classes are analyzed, starting with the voluntary recognition, which is when the parents freely recognize their children. The judicial recognition is analyzed, denominated in the doctrine as forced recognition, which implies the action of the administrator of justice, who after acting the DNA examination, will order the registration of paternity in the Civil Registry. Finally, the testamentary acknowledgment is outlined, which expresses the will of the testator to recognize a child within his testament. In the final part of the investigation the methodology of the work is proposed, mainly what refers to the field research and the results obtained from the survey made to the Judges of the Family, Woman, Childhood and Adolescence of the Riobamba canton.